Mediating factors for student agency: perspectives of school leaders and students - Dang, Minh Tam (Frontiers in Education, 2025)
IntroductionThis study examines the mediating factors that shape student agency in a Confucian Heritage Culture (CHC) context during ongoing education reform in Vietnam. While reforms emphasize student voice and participation, cultural traditions and academic pressures may limit agency in practice.MethodsGrounded in a qualitative case study design, the research drew on semi-structured interviews with six school leaders and open-ended survey responses from 59 secondary students across three types of schools. The adapted Agency of University Students (AUS) scale was used as a coding framework to identify enablers and constraints, with a particular focus on relational and participatory resources.ResultsFindings indicate that school-level reforms created opportunities for greater student participation. However, hierarchical norms, surveillance, and high-stakes academic expectations often constrained students' autonomy. Conversely, trust-based relationships, collaboration, and shared school missions emerged as significant enablers of agency.DiscussionThe results highlight the complex interplay between cultural values and institutional practices in shaping student agency. They suggest that meaningful reform in CHC settings requires not only structural changes in schools but also cultural adaptation to foster authentic student voice and autonomy.